2013
DOI: 10.5098/hmt.v4.2.3001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermoelectric Device Performance Through Integrated Flow Channels

Abstract: In this study, the thermoelectric performance of an integrated thermoelectric device (iTED) with rectangular, round end slots, and circular flow channel designs applied to waste heat recovery for several hot stream flow rates has been investigated using numerical methods. An iTED is constructed with p-and n-type semiconductor materials bonded to the surfaces of an interconnector with flow channels drilled through it. This interconnector acts as an internal heat exchanger directing waste heat from the hot strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…They revealed that using low thermal impedance liquid raised the COP surprisingly, and even when they applied a solid heat sink, the COP obtained was approximately ranging from 0.4-0.6, but when they utilized liquid as the heat sink, the COP leveled by of approximately 0.95-1.85. Recently Reddy et al (2013) also performed an investigation to increase the COP of their thermoelectric cooling system. They found a significant increase in COP or performance.…”
Section: Introduction *mentioning
confidence: 99%
“…They revealed that using low thermal impedance liquid raised the COP surprisingly, and even when they applied a solid heat sink, the COP obtained was approximately ranging from 0.4-0.6, but when they utilized liquid as the heat sink, the COP leveled by of approximately 0.95-1.85. Recently Reddy et al (2013) also performed an investigation to increase the COP of their thermoelectric cooling system. They found a significant increase in COP or performance.…”
Section: Introduction *mentioning
confidence: 99%